2021
DOI: 10.3390/nano11102660
|View full text |Cite
|
Sign up to set email alerts
|

Up-Converting Luminescence and Temperature Sensing of Er3+/Tm3+/Yb3+ Co-Doped NaYF4 Phosphors Operating in Visible and the First Biological Window Range

Abstract: Accurate and reliable non-contact temperature sensors are imperative for industrial production and scientific research. Here, Er3+/Tm3+/Yb3+ co-doped NaYF4 phosphors were studied as an optical thermometry material. The typical hydrothermal method was used to synthesize hexagonal Er3+/Tm3+/Yb3+ co-doped NaYF4 phosphors and the morphology was approximately rod-like. The up-conversion emissions of the samples were located at 475, 520, 550, 650, 692 and 800 nm. Thermo-responsive emissions from the samples were mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The temperature measurements demonstrated the potential for application of the Er 3+ /Tm 3+ /Yb 3+ -codoped NaYF 4 phosphor for temperature determinations in the visible and first biological window ranges. 36 Additionally, Zhen Sun et al confirmed the luminescence mechanism of Li + and Mg 2+ -codoped Bi 3.84 W 0.16 O 6.24 :Tm 3+ , Yb 3+ phosphor with theoretical and experimental analyses. The experimental results showed that this phosphor had a strong UC luminescence intensity and a high temperature sensitivity (optimal sensitivity of 0.1%) in the biological temperature range 298-318 K and can be used as a temperature sensor in the first biological window.…”
mentioning
confidence: 94%
“…The temperature measurements demonstrated the potential for application of the Er 3+ /Tm 3+ /Yb 3+ -codoped NaYF 4 phosphor for temperature determinations in the visible and first biological window ranges. 36 Additionally, Zhen Sun et al confirmed the luminescence mechanism of Li + and Mg 2+ -codoped Bi 3.84 W 0.16 O 6.24 :Tm 3+ , Yb 3+ phosphor with theoretical and experimental analyses. The experimental results showed that this phosphor had a strong UC luminescence intensity and a high temperature sensitivity (optimal sensitivity of 0.1%) in the biological temperature range 298-318 K and can be used as a temperature sensor in the first biological window.…”
mentioning
confidence: 94%
“…[3][4][5] However, the above-mentioned anti-counterfeiting technologies have some disadvantages like poor concealment, complicated manufacturing process, and expensive recognition, which seriously hinder their further applications. Until now, rare earth ion (Re 3+ )-doped luminescent materials with color-tunable performance are extensively used in anti-counterfeiting technology, display, laser, optical temperature measurement, and other fields, especially in the field of anti-counterfeiting and encryption, [6][7][8][9][10] due to these luminescence materials emit some light only under a certain excitation for message encryption. 11,12 However, the nanoscale phosphors may suffer from poor thermal stability and poor mechanical properties in actual applications.…”
Section: Introductionmentioning
confidence: 99%
“…One of them are UCNPs doped with rare-earth ions, which can be excited through multiple electron states and produce luminescence bands in a wide range of the visible (VIS), NIR, and SWIR spectra [28,29]. A significant number of publications are devoted to the study of nanoparticles (NPs) with triple doping, which could be used for multimodal bioimaging with subsequent control of temperature, microenvironment, or probing depth [30][31][32][33][34][35][36][37][38]. Doping with multiple active ions allows for the production of multicolor luminescence with controllable bands upon single wavelength excitation [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%